Defined Intestinal Regions Are Drained by Specific Lymph Nodes That Mount Distinct Th1 and Th2 Responses Against Schistosoma mansoni Eggs - Mayer, Johannes U.; Brown, Sheila L.; MacDonald, Andrew S.; Milling, Simon W. (Frontiers in Immunology, 2020)
The balance of type 1 and type 2 immune responses plays a crucial role in anti-helminth immunity and can either support chronic infection or drive type 2 mediated expulsion of the parasite. Helminth antigens and secreted molecules directly influence this balance and induce a favourable immunological environment for the parasite’s survival. However, less is known if the site of infection also influences the balance of type 1 and type 2 immunity. Here, we report that tissue-specific immune responses are mounted against helminth antigens, which elicited strong IL-4 responses when injected into the skin, while the same antigen, delivered into the intestinal subserosa, induced increased IFN-γ and reduced Th2 responses. Immune responses in individual mesenteric lymph nodes that drain defined regions of the intestine furthermore displayed a site-specific pattern of type 1 and type 2 immunity after Schistosoma mansoni or Heligmosomoides polygyrus infection. S. mansoni egg-specific Th2 responses were detectable in all mesenteric lymph nodes but Th1 responses were only present in those draining the colon, while H. polygyrus infection elicited mixed Th1 and Th2 responses in the lymph nodes draining the site of infection. Similar site-specific type 1 and type 2 immune responses were observed in the draining lymph nodes after the controlled delivery of S. mansoni eggs into different segments of the small and large intestine using microsurgical techniques. Different subsets of intestinal dendritic cells were responsible for the uptake and priming of Th1 and Th2 responses against helminth antigens. Migratory CD11b+CD103- and especially CD11b+CD103+ DC2s transported S. mansoni egg antigens to the draining lymph nodes to induce Th1 and Th2 responses, while CD103+ DC1s induced only IFN-γ responses. In contrast, H. polygyrus antigens were predominantly transported by CD11b+CD103- DC2s and CD103+ DC1s and all DC subsets induced similar Th1 but weaker Th2 responses, compared to S. mansoni egg antigens. The development of adaptive anti-helminth immune responses is therefore influenced by the antigen itself, the uptake and priming characteristics of antigen-positive dendritic cell subsets and the site of infection, which shape the level of Th1 and Th2 responses in order to create a favourable immunological environment for the parasite.